Laboratory XANES to study vanadium species in vanadium redox flow batteries. (December 2020) - Lutz, Christian; Fittschen, Ursula Elisabeth Adriane
Abstract : The speciation of vanadium in the electrolyte of vanadium redox flow batteries (VRFBs) is important to determine the state of charge of the battery. To obtain a better understanding of the transport of the different vanadium species through the separator polymer electrolyte membranes, it is necessary to be able to determine concentration and species of the vanadium ions inside the nanoscopic water body of the membranes. The speciation of V in the electrolyte of VRFBs has been performed by others at the synchrotron by X-ray absorption near-edge structure analysis (XANES). However, the concentrations are quite high and not necessarily justify the use of a large-scale facility. Here, we show that vanadium species in the electrolyte and inside the ionomeric membranes can be determined by laboratory XANES. We were able to determine V species in the 1.6 M electrolyte with a measurement time of 2.3 h and V species having a concentration of 9.8 g kg −1 inside the membranes (178 µm thick) with a measurement time of 5 h. Our results show that laboratory XANES is an appropriate tool to study these kind of samples.